Postural stability and ankle sprain history in athletes compared to uninjured controls - Huurnink, A.; Fransz, D. P.; Kingma, I.; Verhagen, E. A. L. M.; van Dieën, J. H. (Clinical Biomechanics, 2014)
Diminished postural stability is a risk factor for ankle sprain occurrence and ankle sprains result in impaired postural stability. To date, ankle sprain history has not been taken into account as a determinant of postural stability, while it could possibly specify subgroups of interest.